Ict's and Dysgraphia - Gkeka, Eugenia; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The aim of this review is the recognition of characteristics of “Dysgraphia” or “Dysorthography”, as specific learning disorder in written. Concretely, the diagnostic technological tools enable to recognize the particular characteristics of this disorder. As well as, the offer of the intervention technological tools is been evident with the effectiveness of the different applications. Indeed, the activities and the exercises of these tools on educational and game environment using augmented reality assist the children’s and the adults’ handwriting with Dysgraphia and enhance the writing skills.